Evaluation of Information Technology-Based Inclusive Education’s Policies in DIY for the 2017/2018 Academic Year - Asiah, Uswatun; Mutiarin, Dyah (Sustainability (STPP) Theory, Practice and Policy, 2021)
This study aims to reveal and explain the results of the evaluation of information technology-based inclusive education policies in DIY for the 2017/2018 academic year conducted by researchers in 16 high school inclusion schools in DIY. In this study the authors use two major concepts in evaluating this policy, namely: Policy Design and Policy Implementation. The method used in this research is Mix-Method, which combines two qualitative and quantitative research methods, so that more comprehensive, valid, reliable, and objective data are obtained. The results of this study are the policy design obtained a value of 3.12 and was included in the fairly good category, the implementation of the policy obtained a score of 2.77 and was included in the good enough category so that the results of the evaluation of information technology-based inclusive education policies in DIY for the 2017/2018 academic year were in the fairly good category.